Constructing ‘sense of security’ within non-formal youth subculture - Šatūnienė, Reda (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryThere still are no empirical ethnological or anthropological studies on the ‘sense of security’ construction in non-formal subcultural youth groups in Lithuania. The results of the current research offer a premise that organization of non-formal subcultures is influenced by the sense of insecurity. In the paper, the sense of security is taken as a positive experience, a sense of community, proactivity. The main purpose of the paper is to analyze the possibilities and peculiarities of constructing the ‘sense of security’ within the non-formal youth subculture, focusing on the construction of links of trust and creation of a safe social environment. In 2004–2008, an ethnographic research was conducted while preparing a doctoral dissertation at the Vytautas Magnus University. Afterwards, the participation in subcultural activities was found to make one trust more in him / herself and others, help one to express him / herself, strengthen the inner ‘me’. Within the subculture, non-formal links based on trust dominate, thus creating a “safe” social environment.Key words: non-formal subculture, values, sense of security, social organization.